Catecholaminergic polymorphic ventricular tachycardia: risk modulators in patients treated with beta-blockers. (3rd October 2022) - Kukavica, D; Mazzanti, A; Trancuccio, A; Giannini, G; Marino, M; Memmi, M; Gambelli, P; Bloise, R; Morini, M; Ortiz-Genga, M; Napolitano, C; Priori, S G
Abstract: Background: Due to the catecholaminergic nature of arrhythmias that define the Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT), beta-blockers (BBs) represent the first line therapy for this severe arrhythmogenic syndrome. Despite optimal BB therapy, a proportion of patients continue to suffer breakthrough life-threatening arrhythmias (LAE). Purpose: To evaluate the role different classes of BBs (β1-selective vs. non-selective) in LAE reduction and to identify risk factors for breakthrough LAE while on BB monotherapy. Methods: We studied 238 consecutive patients with CPVT and treated with BB monotherapy followed-up prospectively. CPVT was diagnosed according to the 2015 European Society of Cardiology Guidelines. The endpoint was the occurrence of the first LAE (sudden cardiac death, aborted cardiac arrest, or hemodynamically non-tolerated ventricular tachycardia) in BB monotherapy. The follow-up for each patient was calculated from BB therapy start to the occurrence of the endpoint, death from non-arrhythmic cause, the date of last visit, or the initiation of other treatments (i.e.: other antiarrhythmics or left cardiac sympathetic denervation [LCSD]), whichever occurred first. Multivariable Cox proportional hazards model was used to evaluate the effects of history of LAE before diagnosis of CPVT, occurrence of unexplained syncope before diagnosis of CPVT, genotype, and type of BB therapy, as a time-dependent variable, on the risk of experiencing an LAE during BB monotherapy. Results: We enrolled 238 CPVT patients (135 probands, 135 females): 226 with typical CPVT (n=216 RYR2; n=10 CASQ2) and 12 with atypical CPVT (n=5 RYR2-Loss-of-Function, n=4 TRDN and n=3 TECRL). Prior to BB monotherapy, 48/238 (20%) patients had survived an LAE, and 110/238 (46%) patients had experienced an unexplained syncope. During 1, 629 person-years of follow-up during BB monotherapy, 35 patients experienced an LAE (annual LAE rate 2.1%, 95% CI: 1.5%–3.0%; Figure A). Five-year cumulative probability of experiencing an LAE during BB monotherapy was 11.9% (95% CI: 7.0%-16.6%). In this population, multivariable analysis showed that history of LAE before diagnosis (HR 3.6; 95% CI: 1.6–8.1; p=0.002) and syncope before diagnosis (HR 6.1; 95% CI: 2.5–14.9; p<0.001) were clinical risk factors for LAE occurrence. Patients with TRDN mutations were significantly more likely to suffer LAE (HR 20.9; 95% CI: 2.2–196.3; p=0.008). Using nadolol as the gold standard, the use of β1-selective BBs (HR 3.4; 95% CI: 1.4–8.6; p=0.009), but not propranolol (HR: 0.9; 95% CI: 0.2–3.8; p=0.887), was associated with poorer outcome during BB monotherapy (Figure B). Conclusions: In patients with CPVT, selective BBs are associated with a higher risk of LAE as compared to nadolol. Patients who have survived an LAE and/or experienced an unexplained syncope prior to diagnosis, as well as carriers of TRDN mutations are at high risk of BB failure. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ricerca Corrente Funding scheme of the Italian Ministry of Health and Italian Ministry of Research and University Dipartimenti di Eccellenza 2018–2022 grant to the Molecular Medicine Department (University of Pavia).